2008
DOI: 10.1523/jneurosci.1071-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine Exposure Enhances Accumbal Responses to Reward-Predictive Stimuli in a Pavlovian Conditioned Approach Task

Abstract: Acute and repeated exposure to psychostimulants such as amphetamine enhances the effects of pavlovian conditioned stimuli on conditioned behavior. It is hypothesized that amphetamine facilitates conditioned stimulus (CS) effects by selectively enhancing accumbal neuronal responses to stimuli. To test this hypothesis, rats were trained to discriminate between two pavlovian stimuli. One stimulus (i.e., CSϩ) was paired with sucrose delivery [i.e., unconditioned stimulus (US)], and the other stimulus (i.e., CSϪ) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 58 publications
0
17
2
Order By: Relevance
“…These authors suggest that the CS may elicit responding by evoking not only an US representation but also a general appetitive representation. However, even though conditioned approach is enhanced by amphetamine (Wyvell and Berridge 2000;Wan and Peoples 2008), in the present study the CR response became less amphetamine-sensitive with repeated testing. Thus, our results extend and qualify these conclusions and suggest that a generalized appetitive representation is unlikely to maintain CR responding as extinction progresses.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…These authors suggest that the CS may elicit responding by evoking not only an US representation but also a general appetitive representation. However, even though conditioned approach is enhanced by amphetamine (Wyvell and Berridge 2000;Wan and Peoples 2008), in the present study the CR response became less amphetamine-sensitive with repeated testing. Thus, our results extend and qualify these conclusions and suggest that a generalized appetitive representation is unlikely to maintain CR responding as extinction progresses.…”
Section: Discussioncontrasting
confidence: 71%
“…Thus psychostimulants potentiate instrumental responding for natural rewards depending on the reinforcement schedule (Slawecki and Samson 1996), for brain stimulation reward (Gilliss et al 2002) and for reward-predicting stimuli (Sutton and Beninger 1999). Amphetamine selectively enhances nucleus accumbens neuronal firing to a conditioned stimulus (CS) paired with sucrose in a conditioned approach task (Wan and Peoples 2008). On the other hand, CS extinction and unexpected reward omission are associated with a suppression in dopamine cell firing (Schultz et al 1997;Pan et al 2008) and dopamine antagonism results in extinction-like behavior (Wise et al 1978).…”
Section: Introductionmentioning
confidence: 99%
“…An expectation from that reciprocal inhibition view would be that excitatory peaks of VP firing observed here might have corresponded to inhibitory pauses of NAc neurons, which have been suggested to signal reward (20,24,88,89). However, simultaneous excitations in NAc and VP (or simultaneous inhibitions) may also be possible (29,37,62,87,90), perhaps enabled by corelease of peptides such as dynorphin, enkephalin, or substance P to modulate the impact of GABA on postsynaptic neurons (5,6,32,87). Additionally, neurons of the NAc hotspot in the rostrodorsal medial shell may not project directly to neurons in the posterior VP hotspot recorded here but rather, to a more anterior site in VP and to lateral hypothalamus (7) from where interneurons might convey signals to posterior VP to contribute to functional interactions (37).…”
Section: Reward Component Separation By Population Segregation and Fimentioning
confidence: 71%
“…For example, acute AMP administration enhances performance of an instrumental response which was reinforced by presentation of a conditioned stimulus [12]. It has also been demonstrated that post-training administration of amphetamine enhanced consolidation of a Pavlovian conditioned approach response [14], and that acute amphetamine exposure enhances approach to a conditioned stimulus (CS+) associated with liquid sucrose reward but not approach of a stimulus not associated with such reward (CS−), and moreover that such enhanced responding to the CS+ was accompanied by increased magnitude of responding from neurons in nucleus accumbens [23]. These previous studies, however, have employed conditioning procedures where CS and US were delivered in the same location, and thus, sign- and goal- tracking behaviors would be indistinguishable from each other.…”
Section: Differential Effects Of Amphetamine On Sign-tracking and Goamentioning
confidence: 99%
“…After subjects reached a stable level of performance, they were run in the task under five different doses of amphetamine and a saline control. Based on previous studies showing acute amphetamine enhances instrumental responding for conditioned reinforcement [12, 16], and approach of the CS [23], we hypothesized that AMP would enhance sign-tracking with increasing doses (i.e. decrease latency of the behavior, increase number of responses), and, to the extent that goal-tracking and sign-tracking are competing behaviors, decrease goal-tracking (i.e.…”
Section: Differential Effects Of Amphetamine On Sign-tracking and Goamentioning
confidence: 99%